Prolonged cooling for exercise recovery: A novel use for phase change material - Kwiecien, S. Y. (Northumbria University, 2020)
Strenuous exercise can result in structural damage to the skeletal muscle. Muscle damage, which can be experienced by both recreational and elite athletes, is accompanied by signs and symptoms such as strength loss, and increases in soreness, oxidative stress, and inflammation. If excessive or unabated muscle damage can result in performance decrements. Hence, accelerating recovery has been the focus of much research. Cryotherapy has become an increasingly popular recovery modality for its purported ability to reduce blood flow, metabolism and the inflammatory response at the site of the muscle damage. Cold water immersion (CWI) is most commonly used following exercise for reducing muscle soreness, but evidence to support its use for accelerating recovery of strength loss, muscle damage, or inflammation remains conflicting. All cryotherapy modalities are limited in their duration of application. Phase change material (PCM), a novel cryotherapy modality, is capable of overcoming this limitation by extending the duration of treatment for longer than other more traditional cryotherapy modalities. Thus, PCM might present a practical alternative to CWI as a recovery modality. However, the application of PCM for accelerating recovery from exercise has not been examined. Therefore, this course of investigation aimed to elucidate the effects of PCM on recovery from strenuous exercise. Firstly, this research focused on determining the efficacy of prolonged PCM cooling for recovery from mechanically and metabolically stressful exercise. Secondly, the effects of prolonged PCM cooling on intramuscular, core temperature, and the cardiovascular response were determined and compared with a CWI protocol. Finally, this research investigated whether PCM cooling blunted the acute adaptive response to eccentric exercise, following a repeated bout of exercise. Study 1: This study established the proof of concept that wearing a garment fitted with PCM at a temperature of 15°C administered to the quadriceps for 6 hours could improve recovery from damaging eccentric exercise. The PCM treatment was effective in accelerating recovery of strength loss and soreness. Results also demonstrated that prolonged PCM cooling accelerated recovery of these variables in the leg that did not directly receive PCM cooling. This finding suggested that prolonged PCM cooling might deliver a systemic, and not just a local effect. Study 2: This investigation examined the efficacy of PCM as a recovery intervention following exercise with a large metabolic component (a marathon run). Unlike the results from Study 1, recovery of strength loss and perceived soreness were not accelerated from 3 hours of PCM cooling. The results also indicated that PCM cooling was not effective in accelerating recovery of vertical jump height, or blood markers of muscle damage or systemic inflammation. Study 3: This study determined the effects of 3 hours of PCM cooling and 15 minutes of CWI controlled for treatment temperature (15°C PCM and 15 ± 1°C CWI) on intramuscular-, core-, skin-temperature and cardiovascular responses. Although the magnitude of temperature reduction from both PCM and CWI was comparable, PCM maintained a reduction in intramuscular temperature throughout the duration of application. This study also confirmed that, during application, both modalities exerted a central effect on core temperature and heart rate (HR). These effects on core temperature and HR suggested that the effect observed from indirect PCM cooling in Study 1 was a true systemic effect. Study 4: The final study of this thesis expanded on the findings of the pilot study, by repeating the same exercise protocol 2 weeks later, in order to examine whether acute adaptation (the repeated bout effect; RBE) was influenced by the PCM intervention. In contrast to the first investigation, the PCM were applied to both legs in the treatment condition, and blood markers of muscle damage and inflammation were additionally measured. The results demonstrated that PCM cooling accelerated recovery of strength, soreness, and the blood marker of muscle damage, but not inflammation. Importantly, despite accelerating recovery following the first bout of exercise, PCM did not inhibit the RBE. The series of investigations encompassing this thesis have established support for the use of prolonged PCM cooling in accelerating recovery from exercise of a mechanical nature. Further, this thesis provides new additions to the literature on the novel application of PCM as a recovery modality for accelerating recovery of strength loss without inhibiting the adaptive response to exercise.